If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3 + h) + -2(5 + 3h) = 0 (3 * 4 + h * 4) + -2(5 + 3h) = 0 (12 + 4h) + -2(5 + 3h) = 0 12 + 4h + (5 * -2 + 3h * -2) = 0 12 + 4h + (-10 + -6h) = 0 Reorder the terms: 12 + -10 + 4h + -6h = 0 Combine like terms: 12 + -10 = 2 2 + 4h + -6h = 0 Combine like terms: 4h + -6h = -2h 2 + -2h = 0 Solving 2 + -2h = 0 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -2h = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -2h = 0 + -2 -2h = 0 + -2 Combine like terms: 0 + -2 = -2 -2h = -2 Divide each side by '-2'. h = 1 Simplifying h = 1
| -3(y/1)= | | 27x^2+42x-9=0 | | ln(7-x)-ln(3x-1)=1 | | 35-3x=7-10x | | 3/9x | | 4x+9=31-6x | | 6x+-1(-x)=3x+8 | | 4x*5y*2z= | | ln(x+1)+lnx=2 | | 6k+1+5k= | | (3ad/4cd)^-2 | | 2+9x=4x-13 | | x+y+3xy=2015 | | 4a-9b= | | 4z/9-2=0 | | 7x+10y=300 | | (1-w)(5w-6)=0 | | y(y-1)=20 | | 56x^2+54x+10= | | -1.5x^2+24x-22.5=0 | | (5x+8)(x-1)whenx=-5 | | 10+2y=8 | | y=4x^2+2x+3 | | 2x-11y=19 | | 3(5x+3)+1=7x-9(x-3) | | 3x-2x-8=5x+16 | | 3ax+2y=4 | | 7(x-7)+11=3(x-6) | | 2x-2(2x-2)=60 | | 5x-4(9x-2)=90 | | 5x+15-3=x | | 5x-(9x-2)=90 |